LEO PALAYENG - Jadinon, Rémy (International Library of African Music, 2023)
This article examines the historical and sociological processes that led to the electronification of traditional Acholi musical repertoires in the northern region of Uganda. Akena P’Layeng Okella, also known as Leo Palayeng, is presented as a leading figure in this transformation of traditional music to electronic music, which has become known as Acholitronix. Palayeng is also my main interlocutor. Through Palayeng’s biography, the influence of digital technology in the production, distribution, and reception of musical traditions is discussed. The new, digitised repertoire was first integrated into wedding ceremonies, and then played in bars and clubs in the city. It finally reached the international, alternative electronic club scene. This process of transformation in the repertoire is part of a long history of local and international musical influences in Uganda. The extent to which information and communication technologies have played a decisive role in the dissemination of musical genres, the adoption or adaptation of musical instruments and techniques, and the creation of local, national, or even pan-African musical identities since the 1980s, is described in the article. The place that these forms of digital musical traditions have on online platforms is also discussed. Based on these observations, the contours of the transformation and switch from the acoustic to the electronic – while being considered by the actors as being the same music – are described.
Keywords: Electronic music; Festivals; Social networks; Folk music; Digital Technology; Acholi Music; Traditional Music; Uganda; African Music